Multiplex PCR based screening for micro/partial deletions in the AZF region of Y-chromosome in severe oligozoospermic and azoospermic infertile men in Iran - Majid Motovali-Bashi; Zahra Rezaei; Fariba Dehghanian; Halimeh Rezaei (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Infertility is a health problem which affects about 10-20% of married couples. Male factor infertility is involved approximately 50% of infertile couples. Most of male infertility is regarding to deletions in the male-specific region of the Y chromosome. Objective: In this study, the occurrence of deletions in the AZF region and association between infertility and paternal age were investigated in Iranian men population. Materials and Methods: To assess the occurrence of Y chromosomal microdeletions and partial deletions of the AZF region, 100 infertile men and 100 controls with normal spermatogenesis were analyzed. AZFa, AZFb, AZFc and partial deletions within the AZFc region were analyzed using multiplex PCR method. Finally, the association between paternal age and male infertility was evaluated. Results: No AZFa, AZFb or AZFc deletions were found in the control group. Seven infertile men had deletions as the following: one AZFb, five AZFc, and one AZFab. Partial deletions of AZFc (gr/gr) in 9 of the 100 infertile men (9/100, 9%) and 1 partial AZFc deletions (gr/gr) in the control group (1/100, 1%) were observed. In addition, five b2/b3 deletions in five azoospermic subjects (5/100, 5%) and 2 partial AZFc deletions (b2/b3) in the control group (2/100, 2%) were identified. Moreover, the risk of male infertility was influenced by the paternal age. Conclusion: The results of this study suggested that the frequency of Y chromosome AZF microdeletions increased in subjects with severe spermatogenic failure and gr/gr deletion associated with spermatogenic failure.